PENGUATAN KOSAKATA BAHASA INGGRIS DAN AKHLAK ISLAMI MELALUI ISLAMIC STORYTELLING: STRENGTHENING ENGLISH VOCABULARY AND ISLAMIC MORALS THROUGH ISLAMIC STORYTELLING - Jhon Sarip; Zaitun Qamariah; Tiara Nur Fatimah Almadani; Siti Nurrahmah; Ayu Putriana Lestari (Pakis Journal Institute, 2023)
Periodic curriculum changes are a response to the dynamics of changing educational needs. These changes involve all levels of education, including primary schools. In the era of the Merdeka curriculum, English has been introduced since the primary school level, recognising the importance of developing children's linguistic skills early on. The approach used in this community service is Asset-Based Community Development (ABCD). The service stages include observation, team building, preparation, implementation, and evaluation. The evaluation showed significant improvements in students' knowledge of vocabulary, grammar, speaking skills, story comprehension, and moral values during the story and translation sessions. In addition, this activity successfully increased students' active participation in English learning.